2011
DOI: 10.1167/11.14.17
|View full text |Cite
|
Sign up to set email alerts
|

Whether dots moving in two directions appear coherent or transparent depends on directional biases induced by surrounding motion

Abstract: When two random-dot patterns moving in different directions are superimposed, motion appears coherent or transparent depending on the directional difference. In addition, when a pattern is surrounded by another pattern that is moving, the perceived motion of the central stimulus is biased away from the direction of the surrounding motion. That phenomenon is known as induced motion. How is the perception of motion coherence and transparency modulated by surrounding motion? It was found that two random-dot horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…To determine the extent to which discrimination in transparent motion is worse than for nontransparent motion, we ran a control experiment where the motions were not superimposed but instead occupied adjacent spatial regions, and colour-motion coherence was fixed at 100%. Note that, although they were no longer transparent, the two motions in the centre-surround annular display should still be prone to the same interactions underlying direction repulsion, as many studies using this type of stimulus arrangement have shown (e.g., Chen et al., 2014; Kim & Wilson, 1997; Takemura et al., 2011; Wiese & Wenderoth, 2010). Data from five participants as well as the group average in the control experiment are plotted in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the extent to which discrimination in transparent motion is worse than for nontransparent motion, we ran a control experiment where the motions were not superimposed but instead occupied adjacent spatial regions, and colour-motion coherence was fixed at 100%. Note that, although they were no longer transparent, the two motions in the centre-surround annular display should still be prone to the same interactions underlying direction repulsion, as many studies using this type of stimulus arrangement have shown (e.g., Chen et al., 2014; Kim & Wilson, 1997; Takemura et al., 2011; Wiese & Wenderoth, 2010). Data from five participants as well as the group average in the control experiment are plotted in Figure 5.…”
Section: Resultsmentioning
confidence: 99%
“…The representation of such multiple velocity fields at the same region of space is a challenging computational feat, both for the visual system as well as for models that attempt to simulate it (Braddick, Wishart, & Curran, 2002; Garcia & Grossman, 2009; McDonald, Clifford, Solomon, Chen, & Solomon, 2014; Qian, Andersen, & Adelson, 1994; Snowden, Treue, Erickson, & Andersen, 1991; Snowden & Verstraten, 1999). As such, the constraints by which the perception of transparency collapses and the separate moving surfaces are instead misperceived as a single or ‘coherent’ pattern comprise an important focus of research (Suzuki & Watanabe, 2009; Takemura, Tajima, & Murakami, 2011; Williams & Sekuler, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Solid blue: predicted biphasic function for smaller opening angles. (h)–(l) Extended experiment from [39] which surrounds the two central RDKs with additional RDKs in an annulus. The hierarchical inference model replicates human perception in various conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The hierarchical inference model replicates human perception in various conditions. (h) A surround with dots moving vertically both up- and downwards (“bi-directional surround” in [39], indicated by orange arrows in the top-left sketch’s annulus) causes no repulsion in the perceived directions of horizontally moving RDKs in the center (darker orange arrows in the top-left sketch’s center). Our model replicates this perception as shown in the histogram of 200 trial repetitions.…”
Section: Resultsmentioning
confidence: 99%
“…Braddick et al (2002), using a similar stimulus, found that the largest illusion magnitude was produced by a 458 inducer, while angles of 11.258 and 22.58 resulted in a small direction attraction effect. However, overlaid dot patterns presented with a small directional separation are perceived as a single surface moving in the vector average of the two directions, rather than as overlaid patterns moving in different directions (e.g., Felisberti & Zanker, 2005;Greenwood & Edwards, 2007;Mather & Moulden, 1980;Smith, Curran, & Braddick, 1999;Takemura, Tajima, & Murakami, 2011). Hence attraction measured at such small inducing angles may more accurately reflect a strategy of motion vector averaging, rather than direction attraction per se.…”
Section: Discussionmentioning
confidence: 99%